Preliminary assessment of organochlorine pesticide residues in the sediment from serveral estuaries and Tam Giang - Cau Hai lagoon, Thua Thien Hue, 2005 - Van Thi, Tran Thi; Bang, Tran Hai; Hop, Nguyen Van (Vietnam Journal of Chemistry, 2014)
Organochlorine pesticide residue were determined in sediments collected from three estuary zones fowarding Tam Giang - Cau Hai Lagoon, Thua Thien Hue, Vietnam during the dry season in 2005. A total of 10 sediment samples were collected at the river estuaries and along the lagoon. Base on Sediment Criteria of Environmental Protection Agency (US EPA, 1999) [1] and the Canadian Environmental Quality Guidelines (Canadian EQG, 2002) [3], the site specific Sediment Criterion for specific contaminant was derived to help determine what concentrations of chemicals are likely to be associated with adverse biological effects. The concentrations these contaminants were in the range of 0.2 - 8.2 µg/kg sediment for DDTs, 4.9 - 92.4 µg/kg sediment for HCHs, 1.5 - 110 µg/kg sediment for aldrin & dieldrin and 0.6 - 27.9 for endrin. Most of results were exceeded the Sediment Criteria for Human Health Bioaccumulation. Some of them even exceeded the Wildlife Bioaccumulation Criteria and exceeded the Canadian Environmental Quality Guidelines.  The results obtained in this study show that there still exist a variety of organochlorine pesticide residues in the sediments from the estuaries and lagoon of Thua Thien Hue province